The effect of aging on semen parameters in normozoospermic men: A cross-sectional study - Mahmut Ulubay; Muhammet Bahaettin Ulu; Ekrem Akdeniz (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Semen parameters change with age and are reported differently worldwide. Objective: This retrospective cross-sectional study aimed to investigate the semen quality pattern among aging men and the age thresholds for semen parameters. Materials and Methods: The records of men who had normal semen parameters from January 2015-June 2020 were retrospectively evaluated for andrological outpatient at Samsun Training and Research hospital and Gazi hospital in Samsun, Turkey. Adult men meeting the inclusion criteria were divided into 3 groups of I) 18-29 yr (n = 629), II) 30-39 yr (n = 775), and III) 40-49 yr (n = 190). Correlations between age and sperm parameters were then analyzed. Results: A total of 1594 men were enrolled in the study. Significant differences were observed in total sperm numbers, total motility rates, progressive motility rates, nonprogressive motility rates, normal morphology rates, mean semen volume, and sperm concentrations. The parameters of total sperm number, progressive motility rate, and normal morphology rate were significantly higher in group I than in the other 2 groups (p < 0.001, p < 0.001, and p < 0.001, respectively) and in group II compared to group III (p = 0.001, p = 0.003, and p < 0.001), respectively. Mean semen volume and total motility rate were significantly higher in group I than in the other groups (p = 0.001 and p < 0.001, respectively). However, no difference was observed between group II and group III (p = 0.61 and p = 0.04, respectively). Conclusion: Age has a significant impact on semen parameters capable of affecting male fertility, particularly total sperm numbers, the progressive motility rate, and the normal morphology rate.